2012
DOI: 10.1016/j.jpsychires.2011.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal volume and the AKT signaling system in first-episode schizophrenia

Abstract: Activation of the AKT system is specifically associated with hippocampal volume in first-episode schizophrenia, which provides further evidence for the pivotal role of this messenger system in the pathophysiology of psychotic disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 54 publications
1
22
0
Order By: Relevance
“…in 2004, who identified a multi-single-nucleotide polymorphism (SNP) in patients with schizophrenia. Additionally, these researchers found reduced levels of Akt1 expression in patients with schizophrenia, a finding that has been confirmed in several subsequent studies (Balu et al 2012; Blasi et al 2012; Szamosi et al 2012). Genetic variations in Akt1 have been linked to altered brain physiology, behavior and cognition.…”
Section: Introductionsupporting
confidence: 58%
“…in 2004, who identified a multi-single-nucleotide polymorphism (SNP) in patients with schizophrenia. Additionally, these researchers found reduced levels of Akt1 expression in patients with schizophrenia, a finding that has been confirmed in several subsequent studies (Balu et al 2012; Blasi et al 2012; Szamosi et al 2012). Genetic variations in Akt1 have been linked to altered brain physiology, behavior and cognition.…”
Section: Introductionsupporting
confidence: 58%
“…ErbB3, but not ErbB2, mRNA levels were significantly reduced in the lymphoblasts of schizophrenia patients, and it was not associated with the ErbB4 risk haplotype 24 . We showed that impaired NRG1-induced B cell activation correlates with weak physiological habituation of arousal and paranoid ideas 25 , abnormal gating of perceptual information 26 , and decreased hippocampal volume in schizophrenia 27 . Furthermore, additional evidence from animal and human studies suggests that NRG1 may be a key factor in the interplay of neurodevelopment, synaptic plasticity, glutamatergic/GABA-ergic neurotransmission, and immunological mechanisms in schizophrenia 2835 .…”
Section: Introductionmentioning
confidence: 86%
“…In addition, many studies have found genetic association between AKT1 genetic variants and schizophrenia (Emamian et al, 2004; Ikeda et al, 2004; Schwab et al, 2005; Bajestan et al, 2006). A recent study has shown an association between decrease in phosphorylated AKT--total AKT ratio and reduced hippocampal volume in first episode schizophrenia subjects (Szamosi et al, 2012). Significant decreases in protein levels of members in ERK signaling pathway such as Rap1, B-Raf, MEK1, MEK2, ERK1/2 and RSK1 were found in prefrontal cortex of schizophrenia subjects (Yuan et al, 2010).…”
Section: Neuroprotective Roles Of Bdnf/trkb Signalingmentioning
confidence: 99%